Maternal and Perinatal Outcomes in Pregnancy Complicated with Pre- and Gestational Diabetes Mellitus - Maheswara, Ayya; Razmaeda Sarastry; Kristanto, Herman; Julian Dewantiningrum; Putri Sekar Wiyati (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To analyze maternal and perinatal outcomes in pregnancies complicated by pre-gestational and gestational diabetes. Methods: This is an analytical observational study with a cross-sectional design. We examined 57 women, 39 of pre-gestational diabetes mellitus (PGDM) women, and 19 had gestational diabetes mellitus (GDM). The data were analyzed using the chi-square and Fisher’s exact test. Results: There were no maternal deaths in either group. Pre-eclampsia was significantly higher in the PGDM group. Perinatal deaths and asphyxia were the same in both groups. Prematurity was higher in the PGDM group. Neonates of GDM women appeared to be heavier. Intrauterine fetal death (IUFD) rates were higher in the GDM group. Congenital anomalies were found in the GDM group. Conclusion: There were differences in maternal and perinatal outcomes in both groups, namely pre-eclampsia and congenital anomaly.